Omega-3 Polyunsaturated Fatty Acids and Heart Rate Variability - Christensen, Jeppe H. (Frontiers in Physiology, 2011)
Omega-3 polyunsaturated fatty acids (PUFA) may modulate autonomic control of the heart because omega-3 PUFA is abundant in the brain and other nervous tissue as well as in cardiac tissue. This might partly explain why omega-3 PUFA offer some protection against sudden cardiac death (SCD). The autonomic nervous system is involved in the pathogenesis of SCD. Heart rate variability (HRV) can be used as a non-invasive marker of cardiac autonomic control and a low HRV is a predictor for SCD and arrhythmic events. Studies on HRV and omega-3 PUFA have been performed in several populations such as patients with ischemic heart disease, patients with diabetes mellitus, patients with chronic renal failure, and in healthy subjects as well as in children. The studies have demonstrated a positive association between cellular content of omega-3 PUFA and HRV and supplementation with omega-3 PUFA seems to increase HRV which could be a possible explanation for decreased risk of arrhythmic events and SCD sometimes observed after omega-3 PUFA supplementation. However, the results are not consistent and further research is needed.